CD20, CTLA4, CXCL9, IL18RAP, IL-6, SOCS2, and TNF as potential biomarkers for rheumatoid arthritis disease progression: Systematic review of RNA-seq studies - Jairo Javier Jattin Balcázar; Daniel Felipe Galeano Sánchez; Gerardo Quintana López (Heliyon)
Background: rheumatoid arthritis (RA) is an autoimmune disease characterized by the occurrence of numerous and complex molecular events that hinder establishing precise biomarkers to study this disease, however, transcriptomic analysis has revealed new pathophysiological elements, suggesting that this approach may allow to supply this deficiency. Objective: to develop a systematic review of RNA sequencing (RNA-seq) studies on RA in search of potential biomarkers. Methods: a literature review for RNA-seq studies on human RA was conducted using Embase, PubMed, Web of Science, Scopus, and Cochrane databases. Rayyan was used to compile results and the top 5 up/down-regulated differentially expressed genes (DEGs) were discriminated. Results: 7496 articles were obtained across the databases, selecting 79 papers involving 2423 individuals. DEGs were determined to be at least 38125, but 255 and 124 up- and down-regulated DEGs were detected after filtering by the top 5. Most biomarkers described were related to disease progression (61 %), while the most common analysis and tissue studied were principal component analysis (52 %) and blood (39 %), respectively. The expression of CD20, CTLA4, CXCL9, IL18RAP, IL-6, SOCS2, and TNF was found to be modified after therapeutic intervention, suggesting that these are indicators of disease activity and potential therapeutic failure and thus the molecules could constitute potential biomarkers in RA. Conclusion: biomarker research via RNA-seq may allow underpinning molecular events to further understand disease progression and the impact of treatment.